PERANCANGAN GEDUNG BIOSKOP DI KOTA SINTANG - Prasetyo, Denny Agung; Putro, Jawas Dwijo; Muazir, Syaiful (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
One of the districts with the largest population, densest population activities, and supporting economy is Sintang District, West Kalimantan Province with a population of 413,369 people in 2018. The increase in the population of Sintang Regency every year results in a high level of work activity and affects the desire to go to entertainment, recreation and tourism places. Many places can be visited in Sintang Regency, one of which is the Bukit Kelam tour. In today's technological era, the cinema building is one of the solutions for entertainment venues, where the audience can devote all their attentions and feelings to the living picture being witnessed. Therefore, the design of the Cinema Building located in Sintang Regency is a solution to provide a forum for the community to enjoy film shows and provide a modern building concept that is inseparable from the cultural elements in Sintang Regency. The concept of layout outside and inside the building is needed as an attraction to the Cinema Building. The theater building has the appeal of a dynamic building with a rectangular shape that follows the concept of a projector with the use of wood colors to make it look more elegant. In the building, the designer added Dayak and Malay ornaments which were elements of the Cinema Building Design concept so that it was not separated from cultural elements.